KEDUDUKAN MEDIASI BAGI PARA PIHAK DALAM PENYELESAIAN SENGKETA PERTANAHAN UNTUK MENJAMIN KEPASTIAN HUKUM DITINJAU DARI PERATURAN MAHKAMAH AGUNG NOMOR 1 TAHUN 2008 TENTANG PROSEDUR MEDIASI DI PENGADILAN - Farida, Farida (PROGRESIF: Jurnal Hukum, 2016)
Along with the dynamics in the social and political nearly all aspects of the land can be land disputes. This study will describe how The Stance Of Resolution In Mediation Between Conflicting Parties In The Settlement Of Land Dispute To Guarantee Legal Certainty In Term Of Supreme Court Regulation No. 1 Of 2008 On Mediation Procedure In Court and How The Process of Resolving Land Disputes through Mediation Stage. This study uses normative research to the study of literature. In an effort to further strengthen the use of mediation in the Indonesian legal system and minimize the emergence of legal issues that may arise from the use of mediation then supreme court regulation No. 1 Of 2008 in the articles set about mediation and the solved mediation in court and mediation out court